Religion, Civil Service System and Economic Development in Nigeria - Koko, John Clerk; Amadi, Emmanuel Echezolochi (NIU Journal of Humanities, 2026)
Political, social and economic development is impossible without a functional and efficient civil service system. This is because the civil service system is one of the key drivers of policies and programs of government in any nation of the world. However, in recent times, there has been noticeable decline of the quality of civil service in Nigeria occasioned by the influence of some religious practices on the civil service system. The economic losses accruing from such religious practices are inestimable and portend a serious danger to the overall development of the country. Therefore, this paper examines the nexus between religious practices of civil servants and the current decline in quality of civil service system in Nigeria. In particular, the paper investigates how Christians’ and Muslims’ religious practices particularly prayers at the workplace can potentially inhibit socio-political and economic development in the country. Using the methodologies of desk research and critical discussion, the paper underscores the fact that a nation in which civil service system is characterized by religious practices like Nigeria definitely risks socio-political and economic development. The entire paper is hinged on the views of Max Weber’s Spirit of Capitalism, secularization theory, and institutional theory while also incorporating insights from Émile Durkheim, Talcott Parsons, and Sriya Iyer. Overall, the paper argues that to position Nigeria on the path of socio-political and economic development requires a balanced understanding of religious practices by civil servants at the workplace, while law makers should formulate and implement policies that can checkmate religious practices of civil servants in the civil service system.   Keywords: Religion, Civil Service System, Civil Servants, Development and Nigeria.